Enhanced Simulated Moving Bed Reactor Process for Butyl Acrylate Synthesis: Process Analysis and Optimization - Dânia S. M. Constantino (2016)
A novel process design based on the simulated moving bed technology for the synthesis of butyl acrylate (BAc) was investigated in order to get a more competitive industrial process. For that, a fixed-bed reactor was coupled with a simulated moving bed reactor. Reactive separation regions were determined for different conditions of process configurations and feed compositions allowing the optimal operating parameters to be found. Furthermore, the process integration was accomplished and the desorbent (n-butanol) recovery was also investigated ensuring the minimal BAc purity required (99.5% w/w). The viability and competitiveness of this process were evaluated after an economic analysis which showed that it required similar production costs and energy consumption as well for the highest production capacity when compared with other state-of-the-art processes for the BAc synthesis, presented so far.